Design of Checkers Game Using Alpha-Beta Pruning Algorithm - Jofanda, Achmad Naufal Wijaya; Yasin, Mohamad (Universitas Nusantara PGRI Kediri, 2021)
Checkers is a board game that is played by two people which has a purpose to defeat the opponent by eating all the opponent's pieces or making the opponent unable to make a move. The sophistication of technology at this modern time makes the checkers game can be used on a computer even with a smartphone. The application of artificial intelligence in checkers games makes the game playable anywhere and anytime. Alpha Beta Pruning is an optimization technique from the Minimax Algorithm that can reduce the number of branch/node extensions to get better and faster step search results. In this study, a checkers game based on artificial intelligence will be developed using the alpha-beta pruning method. This research is expected to explain in detail how artificial intelligence works in a game. Alpha-beta pruning was chosen because it can search for the best steps quickly and precisely. This study tested 10 respondents to play this game. The results show that the player's win rate was 60% at the easy level, 40% at the medium level, and 20% at the hard level. Besides that, the level of interest in this game was 80% being entertained and 20% feeling ordinary.